Need to study simplification of gastrointestinal medication regimen in cystic fibrosis in the era of highly effective modulators. Issue 3 (7th December 2022) - Sathe, Meghana; Moshiree, Baha; Aliaj, Enid; Lee, MinJae; Hudson, Jessica; Gifford, Alex; Attel, Susan; Gamel, Breck; Freedman, Steven D.; Schwarzenberg, Sarah Jane; Freeman, A. Jay
Abstract: Introduction: The success of highly effective modulator therapy (HEMT) has led to consideration of simpler regimens for people with CF (PwCF) with opportunities to modify burdensome regimens. Despite the intuitive appeal of discontinuing chronic therapies no longer necessary, this process should be pursued systematically to ensure safety, adherence, and validate patient‐centered preferences. We designed a questionnaire to determine the state of use of acid‐suppressive medications (ASM) and pancreatic enzyme therapy (PERT), current self‐withdrawal and provider‐directed withdrawal practices, and interest in a standardized withdrawal study. Methods: In collaboration with CF Foundation (CFF), a questionnaire was developed and distributed to members of Community Voice (CV, comprised of PwCF and their loved ones), and CF providers regarding the need to study simplifying the gastrointestinal (GI) regimen for PwCF on HEMT. Results: Approximately 20‐40% of CV or CF providers have decreased or stopped ASM for those on HEMT. For PERT, CV and CF providers have decreased dose (34%–48% and approximately 25%, respectively) more often than having stopped it altogether (13%–24% and 3%–12%, respectively). Cumulatively, there is interest in pursuing research in this area (86% CV and 89% CF providers) and willingness to enroll in such a study (80% CV and 89% CF providers). Conclusion: Systematically studying the withdrawal of common GI medications, ASM and PERT, is important to CV and CF providers. Decreases in dosing and withdrawal are already taking place without evidence to support this practice. This questionnaire is the first step in designing a GI medication simplification study in PwCF on HEMT.